Constitutive and acquired mechanisms of resistance to immune checkpoint blockade in human cancer. (August 2017) - Bellone, Matteo; Elia, Angela Rita
Highlights: Monoclonal antibodies directed against regulatory pathways in T lymphocytes are revolutionizing medical oncology. Patients affected by melanoma, or non-small cell lung cancers are sensitive to immune checkpoint blockade (ICB). Patients affected by breast, colon and prostate cancers are less sensitive to this therapeutic approach. Several mechanisms of constitutive or acquired resistance to ICB have been identified. Therapeutic strategies stemming from pre-clinical models can improve clinical outcomes for patients resistant to ICB. Abstract: Cancer immunotherapy with monoclonal antibodies directed against regulatory pathways in T lymphocytes has been revolutionizing medical oncology, and the clinical success of monoclonal antibodies targeting either cytotoxic T lymphocyte antigen-4 (CTLA-4) or program death-1 (PD-1) in patients affected by melanoma, Hodgkin's lymphoma, Merkel cell carcinoma, and head and neck, bladder, renal cell or non-small cell lung cancer is way beyond the most optimistic expectation. However, immune checkpoint blockade (ICB) has failed to arrest progression in a consistent amount of patients affected by those tumors, and various histological types, including breast, colon and prostate cancer, are less sensitive to this therapeutic approach. Such clinical findings have fueled massive research efforts in the attempt to identify pre-existing and acquired mechanisms of resistance to ICB. Here we focus on evidences emerging from studies in humans on how tumor cells and the tumor microenvironment contribute to the heterogeneous clinical responses, and we propose strategies stemming from pre-clinical models that might improve clinical outcomes for patients.